KESEJAHTERAAN MASYARAKAT TRANSMIGRAN DI DESA TANJUNG REJO KABUPATEN WAY KANAN PROVINSI LAMPUNG - Ferdian, Komang Jaka; idrus, iqbal aidar (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2017)
The local government agreed Boyolali and the Right Way to do the transmigration program Swakarsa Mandiri in 2006 to communities around Mount Merapi. Transmigration of citizens who participated in independent spontaneous transmigration program came from the village Gedongan Boyolali District of Cempaka Boyolali, Central Java. Communities that participate in the program Transmigration Swakarsa Mandiri as much as 25 families. Transmigration people placed in Way Kanan Regency Tanjung Rejo. The method used in the writing of this article is a qualitative descriptive approach which explains in detail about the welfare of the community in the village of Tanjung Rejo transmigration. Data obtained in the form of primary data in the form of an interview to the citizens and the government transmigration village accompanied by direct observation and secondary data such as documents, and literature.This study explains two things: first, to explain the top of people's lives in the village of Tanjung Rejo migrants. Every citizen is given the house and yard area reached 1,250. Very simple house has a yard that can be planted with seasonal agricultural crops such as cassava or another. The Government also provides land area of one hectare to the Community transmigration. Transmigration community also suffered eviction when it first occupied the house as well as manage the land given by the government. Evictions were carried out by indigenous communities as a result of the land the transmigration community is indigenous community land. The second describes the welfare society in Tanjung Rejo Transmigration. Transmigration displaced people's lives through spontaneous transmigration program has not been fully standalone wellbeing intact. The Society migrants did not get the land certificate from the government or government Tanjung Rejo Way Kanan. Community migrants only awarded the Certificate of Land (SKT) by the government. This then resulted in the transmigration prosperous society.